THE EFFECT OF THE USE OF MIND MAPPING ON STUDENTS' LEARNING INTERESTS IN SOCIAL STUDIES CLASS VII AT SMPN 6 KOTA SOLOK - Putri, Yanda Zakiyah; Putri, Desi Armi Eka; Zora, Fera (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
Students' interest in learning is very important in education, and mind mapping is an effective method of organizing information visually. This study aims to determine the positive and significant influence of the use of mind mapping on students' learning interest in social studies class VII at SMPN 6 Solok City. This type of research is quantitative with an associative approach, involving 64 students from grades VII.2 and VII.3 through total sampling techniques. Data were collected using questionnaires and analyzed by classical assumption tests, including normality, linearity, homocedasticity, and simple linear regression t-tests. The results of the study showed that the significant value of mind mapping was 0.000 < 0.05 and  6.532 while  1.669 was rejected, so it was  rejected and  accepted. This means that there is a positive and significant influence between the use of mind mapping on students' learning interests. About 40.8% of the variation in learning interests was explained by mind mapping, while 59.2% was influenced by other factors. The regression model was obtained with the formula: Y = 23.163(α) + 0.405(X), showing that an increase of 1 unit of mind mapping use increased students' learning interest by 0.405 points, assuming other factors were constant. Based on research, it can be concluded that the use of mind mapping has a positive influence on students' interest in learning. This method helps visualize information and increase participation. Students are advised to continue to develop skills in making mind mapping more interesting and easy to understand.